2012
DOI: 10.1590/s0102-86502012001000004
|View full text |Cite
|
Sign up to set email alerts
|

Lung morphology and growth of rats exposed to tobacco smoke and alcohol

Abstract: PURPOSE:Investigate the morphological effects of chronic exposure to tobacco smoke inhalation and alcohol consumption on the lungs and on the growth of rats. METHODS: Sixty male Wistar rats were divided into four groups: control, tobacco, alcohol, tobacco + alcohol, for a period of study 260 days. Morphological analysis was conducted by optical and electron microscopy. Rat growth was investigated by measuring the snout-anus length, body mass index and body weight. RESULTS:The three groups exposed to the drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In contrast with its potent effects on fibroblasts, romidepsin had little effect on ATII cell number or lamellar bodies, suggesting minimal toxicity on this cell typ e . Lamellar bodies are storage organelles of pulmonary surfactant and their degeneration has been reported as a marker of toxicity and injury for the lung epithelium [ 44 – 46 ]. Our findings are consistent with studies of romidepsin in CTCL where no pulmonary toxicity was reported [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with its potent effects on fibroblasts, romidepsin had little effect on ATII cell number or lamellar bodies, suggesting minimal toxicity on this cell typ e . Lamellar bodies are storage organelles of pulmonary surfactant and their degeneration has been reported as a marker of toxicity and injury for the lung epithelium [ 44 – 46 ]. Our findings are consistent with studies of romidepsin in CTCL where no pulmonary toxicity was reported [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, since the positions of the OCs are not adjustable, it has the possible limitation of yielding inaccurate SAB measurements for animals with body lengths greater than 26 cm. Indeed, it has been reported that male Wistar rats can attain an average body length of 28.2 ± 0.9 cm (SD, n = 14) when they reach a weight of 593 ± 65 g (Magnani et al, 2012). Despite the last possibility, it should be noted that the studies of continuous SAB in adult rats are usually performed in animals weighing no more than 300 g (Drew et al, 1973;Hefco et al, 2003;Krebs-Kraft & Parent, 2008;Stefani et al, 1999), presumably with a body length of less than 26 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that both low birth weight (LBW) and respiratory infections in infancy were associated with decreased adult lung function and death from COPD [Barker et al 1991]. Evidence to support the concept of ‘foetal programming’, whereby insults during critical periods of development produce permanent structural, physiological or epigenetic changes with lifelong consequences [Miller and Marty, 2010; Barker, 2012], has also been provided by experimental animal models [Kallapur and Ikegami, 2006; Kramer et al 2009; Shimoda and Semenza, 2011; Abbott and Winzer-Serhan, 2012; Hilgendorff et al 2012; Magnani et al 2012; Maritz and Mutemwa, 2012; Sutherland et al 2012]. These studies have shown that insults to the developing lung during intrauterine or very early postnatal life lead to increased susceptibility to respiratory disease during both childhood and later life [Gluckman et al 2008; Harding and Maritz, 2012].…”
Section: Introductionmentioning
confidence: 99%